Cancer among women of reproductive age in Nigeria - Obiora, Uchendu Jude (Asian Journal of Medical Sciences, 2020)
Background: Cancer in women of reproductive age is a poorly addressed but often preventable public health issue. Aims and Objectives: The study aims at analyzing cancer pattern among these women in the apex hospital in Delta State, Nigeria. Material and Methods: The study is a 70-months descriptive retrospective study of histologically confirmed cases of cancer among women of 12-49 years (2014-2019). The corresponding age, organ and histologic diagnosis were examined and subsequently analyzed using excel spreadsheet 2007. The result was presented in tables. Result: The author encountered 224 cancer cases among these women, representing 10% of all surgical specimens during the study period. The age range mean age of these women were 12-49 and 39.09 years respectively. Breast, Colorectal, cervical, ovarian, skin, soft tissue and thyroid cancer accounted for 130(58%), 24(10.7%), 16(7.1%), 11(4.9%), 10(4.5%), 9(4%) and 7(3.1%) of the cases respectively. Those in the 2nd, 3rd, fourth and fifth decades were 2(0.9%), 18, (8%), 96(42.7%) and 109(48.4%) cases respectively. Conclusion: Cancer is relatively common among women of reproductive age, but mostly affected the breast, colorectum, uterine cervix, ovary, skin, soft tissues and thyroid gland. There is need for all hands to be on deck to reverse the trend and improve the lives of those affected by the disease.